Retention of Zinc by Coarse and Medium Textured Soils of Semi-Arid Tract in Western Uttar Pradesh - Singh, Mahendra; Ram, Nand (Annals of Arid Zone, 2016)
In coarse and medium textured soils. retention of Zn followed Langmuir isotherm. Retention capacity and the bonding energy constant varied from 632 to 1587 Zn g’l soil and 0.151 to 0.280 mI ug-1Zn. respectively. The Zn retention capacity correlated very well with organic CEC, clay and sand. Soils extremely rich in sand hut poor in clay and organic matter had relatively lower capacity to fix Zn.